Expose, Oppose, Propose: Alternative Policy Groups and the Struggle for Global Justice - by William K. Carroll - Muhr, T. (Socialist Studies/Études Socialistes, 2020)
The organic crisis of hegemonic neoliberal globalization, manifested in aggravated uneven development condensed with ecological unsustainability, requires systemic transformation towards justice globalism. William Carroll’s distinguished 4- year research project integrates network analysis with qualitative interviewing to depict a rich picture of the contribution of counter-hegemonic knowledge production and mobilisation by transnational alternative policy groups (TAPGs) to such an emancipatory alternative future. Grounded in thorough data analysis, dialogue between neo-Gramscian methodology and the empirical makes this book an indispensable resource for proponents of global justice as it overcomes the disempowering voluntaristic localism and anti-statism that underlies much of both mainstream and critical approaches to “progressive” social transformation.